Exploring Black Feminist Themes in the Works of Toni Morrison and Gloria Taylor (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Exploring Black Feminist Themes in the Works of Toni Morrison and Gloria TaylorSapna Rani; Dr.Raja*This paper explores the impressive range of elastic threads in Black feminist themes threaded through racialist fiction works by Toni Morrison and Gloria Taylor. This book offers a comparative reading of the work by these writers, critiquing their representation and use of race alongside gender while drawing out similarities in how each addresses questions of identity-policing as well privilege. The paper analyzes selected texts to demonstrate the contribution Morrison and Taylor make in engaging with discourses of Black feminism, offering a unique critical lens into the experiences lived out by black woman living within patriarchy. This is a theorectical paper that utilizes both thematic analyses, and critical comparative analysis to draw on 18 scholarly sources in four tables analyzing similar findings avoiding repetion.